Physiological impact of water deficit during growth stages of the wheat crop - AL-SAIDAN KHUDHAIR JOUDAH YASIR (University of Thi-Qar Journal of agricultural research, 2024)
To know the physiological impact of water deficit  during the growth stages of the wheat crop, this study was conducted using plastic pots through the growing season 2023-2024. A split plot design was used. The primary lot comprised water deficit periods (ID) (26/11–25/12 ID1), (26/12–24/1 ID2), (25/1–24/2 ID3), and (25/2–25/3 ID4)) while the sub plots included five wheat varieties (C) (Al-Rashid (C1), Bohouth 22 (C2), Ibaa 99 (C3), Abu Ghraib (C4), and Bora (C5)) on three replicates. The deficit period (ID2) produced the lowest averages for height of plant, amount of chlorophyll, area of flag leaves, tillers number, grain spike number, and the total grain yield (96.07 cm, 0.6780, 44.62 cm2, 320.9 tiller.m2, 61.80  grain.spike-1, 5.757 ton.ha-1) respectively. The water deficit period (ID4) gave the lowest average weight of 1000 grains, which amounted to 39.09 g. Al-Rasheed variety achieved greatness by providing the highest average height of plant, content of chlorophyll , and flag leaf area (108.50 cm, 0.7475, 58.32 cm2), respectively. Bohouth variety gave the highest averages for the number of tillers, the number of grains per spike, and grain yield (406.2 tiller.m2, 66.58  grain.spike-1, 7.464 ton.ha-1). The Ibaa variety provided the greatest average weight of 1000 grains (44.17 g). The interaction treatment ID2C4 provided the least mean of grain yield 5,100 ton.ha-1, while ID1C2 provided the greatest average, this was not very different from ID1C1 (8.847 - 8.463) ton.ha-1. Attention must be paid to the growth periods of the wheat crop that are most affected by water deficit (ID2, ID4) and try to provide water needs for them compared to the periods (ID1, ID3) because they have a significant impact on the overall production.